User Behavior Analysis of E-Wallet Usage Among Generation Z using the Theory of Planned Behavior - Raditya, Muhammad Zacky; Fronita, Mona; Saputra, Eki; Megawati, Megawati; Anofrizen, Anofrizen (SISTEMASI, 2025)
With the rapid advancement of digital technology and the growing demand for fast and practical transaction systems, the use of digital wallets (E-Wallets) among the younger generation—particularly Generation Z—has significantly increased. This study aims to identify the behavioral factors influencing E-Wallet usage among Gen Z by applying the Theory of Planned Behavior (TPB). This theoretical framework includes three main constructs believed to influence Behavioral Intention (BI) and actual user behavior: Attitude Toward the Behavior (ATB), Subjective Norm (SN), and Perceived Behavioral Control (PBC). The study involved 100 Gen Z university students in Pekanbaru, selected through purposive sampling. A quantitative research method was employed, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Instrument validity was tested through discriminant validity, while reliability was assessed using Cronbach’s Alpha and Composite Reliability. The findings reveal that all three variables—Attitude Toward the Behavior, Subjective Norm, and Perceived Behavioral Control—have a significant influence on Behavioral Intention to use E-Wallets among Gen Z in Pekanbaru. Furthermore, both Behavioral Intention and Perceived Behavioral Control significantly affect the actual usage behavior of E-Wallets. Theoretically, these results support the applicability of the TPB framework in the context of digital payment systems. Practically, E-Wallet providers are advised to focus on enhancing users’ positive attitudes, leveraging social influence, and improving ease of use for Gen Z. However, this study is limited by its exclusion of external factors beyond the TPB model that may also influence E-Wallet usage behavior.